Soluções no suprimento de energia elétrica para shoppings centers na Bahia - Ferreira, Humberto Meneses (2009)
From a survey done in four Shopping Malls located in Bahia State, this dissertation is an investigation proposal, under a technical-economic bias have seen that the majority of companies aims to reduce costs - the implementation and use of various forms of alternative energy (Cogeneration and/or energy systems) that enable cost reduction and are applicable to Shopping Malls. This work analyzed the patterns of electrical charge used, the physical structure, weather conditions and marketing for the supply of energy fuels in various ventures studied. This analysis concludes that the use of hybrid systems optimizes the power consumption used, addressing the possibilities of house electricity production and existing regulatory models